Peran Single Parent dalam Membentuk Karakter Religius Anak - Ruslan; Lailatus Shiddiqah (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2024)
Single parents often encounter obstacles in educating children at home. Usually due to lack of knowledge and time because they have to work. This study aims to describe the single parent method in shaping the character of religious children in Karduluk Village, Sumenep and it’s implications. This research uses a qualitative approach with a type of field research. Collecting data using interviews and non-participant observation. The data analysis technique consists of 3 stages, namely data condensation, data display, and conclusion/verification. The research findings show that: first, the role of single parents in shaping the religious character of children in Karduluk Village, Sumenep is carried out through 3 synergistic approaches, namely the advice approach, the exemplary approach, and the habituation approach; second, the role of single parents in shaping the religious character of children in Karduluk village, Sumenep has implications for 3 main aspects, namely the aspect of faith in the form of increasing confidence in children in the existence of Allah SWT; aspects of worship in the form of children's religious behavior that can be seen from their daily lives both in terms of mahdhah worship and ghairu mahdhah worship; and moral aspects in the form of children's attitudes and behavior that reflect religious values ​​and teachings.